2022
DOI: 10.1039/d1cc07242k
|View full text |Cite
|
Sign up to set email alerts
|

Mn-incorporated nickel selenide: an ultra-active bifunctional electrocatalyst for hydrogen evolution and urea oxidation reactions

Abstract: We report Ni-Mn-Se supported on Ni foam as a highly active and stable bifunctional electrocatalyst that exhibits overpotentials of 28 and 122 mV for reaching the current density of 10...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…On the other hand, despite the demonstration of good electrocatalytic activity for OER and UOR by the state-of-the-art RuO 2 and IrO 2 electrocatalysts, their commercial implementation is limited by the high cost and scarcity of these noble metal-based compounds [ 36 ]. Recently, various transition metal-based materials, such as sulfides [ 37 , 38 , 39 , 40 ], oxides [ 10 , 41 , 42 ], selenides [ 43 , 44 , 45 ] and metal–organic frameworks (MOFs) [ 11 , 46 ] have been investigated with noteworthy catalytic performance for UOR. However, they hardly fulfill the requirement for practical implementation due to their high overpotential and low current densities [ 23 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, despite the demonstration of good electrocatalytic activity for OER and UOR by the state-of-the-art RuO 2 and IrO 2 electrocatalysts, their commercial implementation is limited by the high cost and scarcity of these noble metal-based compounds [ 36 ]. Recently, various transition metal-based materials, such as sulfides [ 37 , 38 , 39 , 40 ], oxides [ 10 , 41 , 42 ], selenides [ 43 , 44 , 45 ] and metal–organic frameworks (MOFs) [ 11 , 46 ] have been investigated with noteworthy catalytic performance for UOR. However, they hardly fulfill the requirement for practical implementation due to their high overpotential and low current densities [ 23 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As presented in Figure d, the | Z | fluctuation is relatively constant for the NiFeSbP electrode, verifying that the surface of the NiFeSbP electrode has more aerophobicity than the pure Ni electrode. The increment in the specific resistance corresponds to the accumulation of H 2 bubbles on the electrode surface, while the sudden decrease in the specific resistance is related to the release of bubbles …”
Section: Resultsmentioning
confidence: 99%
“…22 On the other hand, superior electrochemical performance can be obtained by integrating foreign metallic elements into the host material and formulating their chemical composition and morphology. 23,24 Therefore, the simultaneous incorporation of Fe and Sb into Ni−P can regulate the charge distribution of Ni−P and give rise to conductivity, which, to the best of our knowledge, has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Maleki et al [ 99 ] reported a highly active and stable bifunctional electrocatalyst of Ni-Mn-Se in NF and displayed overpotentials of 28 and 122 mV at 10 mA cm −2 for the HER and UOR, respectively. Additionally, it showed an overall urea-splitting voltage of 1.352 V at 10 mA cm −2 .…”
Section: Bifunctional Electrocatalysts For the Uor And Hermentioning
confidence: 99%